2010
DOI: 10.1007/s11060-010-0484-2
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and temozolomide combination in the treatment of leptomeningeal carcinomatosis from ethmoid sinus intestinal-type adenocarcinoma

Abstract: Intestinal-type adenocarcinoma of the nasal cavities and paranasal sinuses is a relatively rare tumor. Standard therapeutic modalities include surgery followed by radiotherapy, sometimes with chemotherapy treatment. Despite these treatments, the outcome is poor due to frequent local recurrences constituting the main cause of death among patients; leptomeningeal carcinomatosis is not a frequent event, and its presence indicates short expected survival. The therapy of neoplastic meningitis includes cranial irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In addition, published case report studies have proven the efficiency of Temozolomide. 25,26 Therefore, oral temozolomide was well-tolerated in this patient.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, published case report studies have proven the efficiency of Temozolomide. 25,26 Therefore, oral temozolomide was well-tolerated in this patient.…”
Section: Discussionmentioning
confidence: 76%
“…These preclinical and clinical studies suggest that cisplatin may enhance the antitumor activity of temozolomide. There are two other factors also contributing to the rationale for the combination of temozolomide and cisplatin: both showed activity against ependymoma [1,5,14] and other brain tumors; in prior studies, this combination was found to have been well tolerated [7,8,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this regimen was that cisplatin might enhance the antitumor activity of temozolomide with a favorable safety profile [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…[12] Platinum drugs can inhibit MGMT transcription and downregulate the expression of MGMT. [13] This is the basis for the synergistic effect of temozolomide and platinum drugs. So, nedaplatin was added to our chemotherapy in an attempt to improve upon therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%